Continuity vs. Discontinuity: A Case of Home Language and Literacy Socialization in Indonesia - Hamida, Layli; Patria, Aditya Nur; Reswari, Girindra Putri Ardana (OKARA: Jurnal Bahasa dan Sastra, 2024)
The present study explores the language and literacy socialization (LLS) of Indonesian children from low- to middle-income families. The Indonesian government has never truly involved home and family as the base for literacy socialization in its programs, affecting the nation-state’s low rank in literacy proficiency. This paper aims to describe the LLS of low- to middle-income Indonesian families and examine how the language used by caregivers and parents stimulates the issue of continuity or discontinuity between home and school literacy practices. The study used an ethnographic approach in which the researchers observed the LLS events of 6 families in Surabaya, Indonesia. Conversations between caregivers/parents and children during literacy events were recorded. The findings suggest that every family has different patterns of literacy practices depending on their beliefs and culture at home and that parents’ or caregivers’ language and style of communication may facilitate or hinder children’s access to literacy. Two socialization patterns were identified, including reference to past experience and collaborative negotiation of meaning. It is argued that not only the background of education but also caregivers’ literacy culture and educational beliefs play a role in their strategy of language and literacy socialization at home.